Sediment Remediation Using Activated Carbon: Effects of Sorbent Particle Size and Resuspension on Sequestration of Metals and Organic Contaminants. (25th February 2022) - Rämö, Robert; Bonaglia, Stefano; Nybom, Inna; Kreutzer, Anne; Witt, Gesine; Sobek, Anna; Gunnarsson, Jonas S.
Abstract: Thin‐layer capping using activated carbon has been described as a cost‐effective in situ sediment remediation method for organic contaminants. We compared the capping efficiency of powdered activated carbon (PAC) against granular activated carbon (GAC) using contaminated sediment from Oskarshamn harbor, Sweden. The effects of resuspension on contaminant retention and cap integrity were also studied. Intact sediment cores were collected from the outer harbor and brought to the laboratory. Three thin‐layer caps, consisting of PAC or GAC mixed with clay or clay only, were added to the sediment surface. Resuspension was created using a motor‐driven paddle to simulate propeller wash from ship traffic. Passive samplers were placed in the sediment and in the water column to measure the sediment‐to‐water release of polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), and metals. Our results show that a thin‐layer cap with PAC reduced sediment‐to‐water fluxes of PCBs by 57% under static conditions and 91% under resuspension. Thin‐layer capping with GAC was less effective than PAC but reduced fluxes of high–molecular weight PAHs. Thin‐layer capping with activated carbon was less effective at retaining metals, except for Cd, the release of which was significantly reduced by PAC. Resuspension generally decreased water concentrations of dissolved cationic metals, perhaps because of sorption to suspended sediment particles. Sediment resuspension in treatments without capping increased fluxes of PCBs with log octanol–water partitioning coefficient ( K OW ) > 7 and PAHs with log  K OW of 5–6, but resuspension reduced PCB and PAH fluxes through the PAC thin‐layer cap. Overall, PAC performed better than GAC, but adverse effects on the benthic community and transport of PAC to nontarget areas are drawbacks that favor the use of GAC. Environ Toxicol Chem 2022;41:1096–1110. © 2022 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.